Pan‐Cancer landscape of protein activities identifies drivers of signalling dysregulation and patient survival. Issue 3 (23rd January 2023) - Sousa, Abel; Dugourd, Aurelien; Memon, Danish; Petursson, Borgthor; Petsalaki, Evangelia; Saez‐Rodriguez, Julio; Beltrao, Pedro
Abstract: Genetic alterations in cancer cells trigger oncogenic transformation, a process largely mediated by the dysregulation of kinase and transcription factor (TF) activities. While the mutational profiles of thousands of tumours have been extensively characterised, the measurements of protein activities have been technically limited until recently. We compiled public data of matched genomics and (phospho)proteomics measurements for 1, 110 tumours and 77 cell lines that we used to estimate activity changes in 218 kinases and 292 TFs. Co‐regulation of kinase and TF activities reflects previously known regulatory relationships and allows us to dissect genetic drivers of signalling changes in cancer. We find that loss‐of‐function mutations are not often associated with the dysregulation of downstream targets, suggesting frequent compensatory mechanisms. Finally, we identified the activities most differentially regulated in cancer subtypes and showed how these can be linked to differences in patient survival. Our results provide broad insights into the dysregulation of protein activities in cancer and their contribution to disease severity. Synopsis: Estimation of activity changes for over 500 kinases and transcription factors in more than 1, 000 cancer samples and cell lines identifies signalling regulators often dysregulated in cancer associated with patient survival. Matched data for changes in DNA, RNA and (phospho)proteins are compiled from publicly available data across 1, 000 tumour samples. Changes in activity for over 500 kinases and transcription factors identify often dysregulated activities in cancer. Recurrent mutations in kinases and transcription factors are not often associated with significant changes in their known targets Signalling regulators within the same pathway tend to be co‐regulated, and activities can be used as predictors of patient survival. Abstract : Estimation of activity changes for over 500 kinases and transcription factors in more than 1, 000 cancer samples and cell lines identifies signalling regulators often dysregulated in cancer associated with patient survival.